2014
DOI: 10.1097/cad.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-release protamine sulphate-impregnated microspheres may reduce the frequent administration of recombinant interferon α-2b in ovarian cancer

Abstract: Parenteral administration of recombinant interferon-α-2b (rINF-α-2b) at a dose of 50×10 IU once a week for 8 weeks is recommended for ovarian cancer. However, short half-life, small therapeutic index and proteolytic degradation cause fluctuations in plasma level and pose barriers in the development of a clinically viable dosage form. Therefore, in the present investigation, fluorescein isothiocynate-tagged rINF-α-2b was loaded into stearic acid (*rINF-α-2b-SMs), pectin (*rINF-α-2b-PMs) and gelatin (*rINF-α-2b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The microencapsulation process achieved less than 60% encapsulation efficiency in several formulations [101,113], while a reduction in biological activity was observed in some cases [93,100,106]. In other formulations, the drug was released abruptly or incompletely [94,99,130].…”
Section: Ifn γmentioning
confidence: 98%
“…The microencapsulation process achieved less than 60% encapsulation efficiency in several formulations [101,113], while a reduction in biological activity was observed in some cases [93,100,106]. In other formulations, the drug was released abruptly or incompletely [94,99,130].…”
Section: Ifn γmentioning
confidence: 98%
“…In vivo assays in Sprague–Dawley rats of this formulation showed that plasma levels of the molecule were stable for 13 days, starting with a rapid release on the first day [ 132 ]. In 2014, Gulia et al impregnated protamine sulfate to gelatin microspheres to increase the release time of IFN-α to 336 h and prolong the in vitro cytotoxic effect on ovarian cancer SK-OV-3 cells [ 133 ]. Chen et al (2016) proposed a different structure by formulating chondroitin sulfate and PVP microneedles that had stability for two months and did not cause skin damage after subcutaneous administration in SD rats [ 134 ].…”
Section: Recent Encapsulation Forms Of Ifnsmentioning
confidence: 99%
“…Despite the positive results obtained in in vitro and in vivo studies of microencapsulations, none of them were evaluated in clinical trials except for Locteron, since they presented drawbacks at different levels. The microencapsulation process achieved less than 60% encapsulation efficiency in several formulations [ 130 , 136 ], while a reduction in biological activity was observed in some cases [ 119 , 129 , 133 ]. In other formulations, the drug was released abruptly or incompletely [ 120 , 128 , 141 ].…”
Section: Recent Encapsulation Forms Of Ifnsmentioning
confidence: 99%
“…On the other hand, the use of type-I IFN has been poorly effective, largely due to toxic effects. To overcome the systemic sideeffects, several IFN delivery systems have been developed, such as the conjugation with polyethylene glycol (PEG) [13,19], gene delivery by albumin fusion protein [20], and microspheres for a constant release [21,22].…”
Section: Introductionmentioning
confidence: 99%